Pengukuran Kinerja Perpustakaan Dengan Pendekatan Balanced Scorecard - Vera Devani (Jurnal Ilmiah Teknik Industri, 2016)
This research aims to investigate, identify and describe the performance level and the factor which impacts to the performance of the Perpustakaan Tun Seri Lanang (PTSL) using Balanced Scorecard approach. The descriptive analysis was used to proceed data on 4 perspectives, were financial, customer, internal business process and learning and growth, respestively. The questionnaires were distributed to 24 employees and 120 questionnaires were distributed to customers. The finding shosw that performance level of PTSL is in good category by the total score 41.75. Performance level of another perspective shows financial performance is very good by the total score 9, customer performance is good by the total score 3.62, internal business process performance is very good by the total score 8.79 and learning and growth performance is good by the total score the 19.34. Based on findings recommendation is formulated in order that PTSL should focus on employee productivity and customer satisfaction.